Kontra-Radikalisasi Agama Pusat Studi Al-Qur’an Jakarta - Fadal, Kurdi (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2020)
This paper describes the effort of the Center for Qur’anic Studies (PSQ) Jakarta in counter-radicalism by mediating the Islamic moderation. The initiated programs of the PSQ have been managed for making an equilibrium of the radical movement in the Muslim community. The research argues that the PSQ emphasizes a soft approach to counter-radicalisation by delving into the Quranic values of moderation and tolerance. There are two primary programs of the PSQ: caderization (as a prospective mufasir) and direct preaching. The programs involve various segments of communities conforming to their educational levels or competencies in the Quranic studies. Education for Young Exegetes (Pendidikan Kader Mufasir: PKM) is an important program for master and doctoral students in writing their thesis; Post-Memorization of the Quran (Pasca-Tahfidz) is a program for those who commit to memorize the Quran; the Daurah Bidayatul Mufassir program for undergraduate students; the Training of Trainer (ToT) program for teachers of the Quran and Islamic preachers; and the Living Quran for high school students. The direct preaching program is designed to provide guidance and assistance to the community in the Friday preaching sermons, seminars, and religious teachings.